Writing material culture history - Gerritsen, Anne (Bloomsbury Academi, 2015)
Writing Material Culture History examines the methodologies currently used in the historical study of material culture. Touching on archaeology, art history, literary studies and anthropology, the book provides history students with a fundamental understanding of the relationship between artefacts and historical narratives. The role of museums, the impact of the digital age and the representations of objects in public history are just some of the issues addressed in a book that brings together key scholars from around the world. A range of artefacts, including a 16th-century Peruvian crown and a 19th-century Alaskan Sea Lion overcoat, are considered, illustrating the myriad ways in which objects and history relate to one another. Bringing together scholars working in a variety of disciplines, this book provides a critical introduction for students interested in material culture, history and historical methodologies"-